Vaccines against COVID-19 using nanotechnology: a literature review - dos Santos, André Flores; Fraga, Alessandra Soares Ayres; Gomes, Patrícia; Fagan, Solange Binotto (Disciplinarum Scientia | Naturais e Tecnológicas, 2021)
In March 2020, it was declared a state of pandemic coronavirus disease (COVID-19) by the World Health Organization, which represents a public health concern. Some vaccines were created to fight the COVID-19 disease and use nanotechnology in their composition. Vaccines approved in clinical trials that are currently available for the population using nanotechnology are BNT162b2 (Pfizer, 95% effective), and mRNA-1273 (Modern, 94, 5% effectiveness). These vaccines use lipid nanoparticles, loaded with RNA (mRNA) to fight SARS-Cov-2. Nanotechnology can have several advantages in creating vaccines, for example, antigen protection by premature degradation to increase the immune response, control release kinetics, provide site-specific antigens, and facilitate intracellular absorption. This review article seeks to present applications of nanostructures in the production of vaccines against COVID-19 that are in the clinical testing phase and also those that have already been approved.